Analysis of Personal Branding Content Creators on @vinamuliana's Instagram Account - Novianti, Anandita Putri; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
Advances in communication technology have given rise to social media platforms such as Instagram, which are now used for personal branding, one of which is Vina Muliana. Vina, a professional in the HR field at BUMN, is also successful as a content creator. With the Instagram account @vinamuliana which is followed by 1.4 million people, Vina actively shares educational content related to careers, including tips for applying for jobs, making CVs and job interviews. This research aims to analyze Vina Muliana's personal branding through her Instagram using the eight main concepts of personal branding according to Montoya. This research uses a qualitative descriptive method, focusing on personal branding analysis and the research object is the Instagram account @vinamuliana. Data was collected through observation and interviews, which was then analyzed using a classification based on the theory of eight personal branding concepts. The results show that Vina Muliana succeeded in implementing these concepts well through her content. Vina stands out in career discussions, showing strong leadership, a friendly and energetic personality, and distinguishing herself from other content creators with a focus on education. Consistency and determination in maintaining her personal branding, coupled with the ethics and good intentions that Vina shows, make her content very useful for her followers.